2014
DOI: 10.5603/kp.a2013.0316
|View full text |Cite
|
Sign up to set email alerts
|

Flow-mediated dilatation (FMD) and prevalence of cardiovascular risk factors: the value of FMD assessment in high risk patients is limited

Abstract: FMD is related to the number of traditional CVRF/CVDs; however, coronary artery disease has the most significant influence on FMD decrease among analysed factors. The value of FMD assessment in high risk patients is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The metabolic profile of the analysed group was not optimal, which, unfortunately, is quite common in the CAH population [14]. The question of whether optimal hormonal status of CAH patients improves endothelial function, which is sensitive to minor homeostasis disturbances, remains unanswered [32].…”
Section: Discussionmentioning
confidence: 96%
“…The metabolic profile of the analysed group was not optimal, which, unfortunately, is quite common in the CAH population [14]. The question of whether optimal hormonal status of CAH patients improves endothelial function, which is sensitive to minor homeostasis disturbances, remains unanswered [32].…”
Section: Discussionmentioning
confidence: 96%
“…No statistically significant difference was detected in subjects with number of risk factors for the value of FMD. Mizia-Stec K et al 25 reported FMD was related only in low risk subjects and no correlation was found in patients with more number of risk factors. Similar findings were noted by Witte DR 26 .…”
Section: Discussionmentioning
confidence: 94%
“…Endothelial dysfunction leads to vascular disease which has been considered as a primary characteristic in the development of atherosclerosis and an independent predictor of poor prognosis in CVD (Cai and Harrison, 2000; Suwaidi et al , 2000). Endothelium-dependent vascular function is assessed by brachial flow-mediated dilation (FMD) and is inversely associated with the future CVD events (Ras et al , 2013; Jambrik et al , 2004; Mizia-Stec et al , 2014).…”
Section: Introductionmentioning
confidence: 99%